Pengaruh Pengungkapan Green Intellectual Capital dan Corporate Social Responsibility Mikro terhadap Kinerja Keuangan - Kangdra, Natasya; Afriyenti, Mayar (Jurnal Nuansa Karya Akuntansi, 2023)
This research examines the effect of Green Intellectual Capital disclosure and Micro Corporate Social Responsibility on financial performance (empirical study on manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2022 period). The population of this research is manufacturing companies listed on the Indonesia Stock Exchange. The sample of this research is 14 manufacturing companies. The source of data in this research is secondary data. Data collection techniques from company annual and sustainability reports. Data analysis using multiple linear regression analysis. The results showed that disclosure of Green Human Capital, Green Structural Capital, Micro Corporate Social Responsibility has no effect on the financial performance of manufacturing companies listed on the Indonesian Stock Exchange, meanwhile disclosure of Green Relational Capital has a positive effect on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange.